PERANCANGAN SISTEM INFORMASI KELENGKAPAN REKAM MEDIS RAWAT JALAN DENGAN METODE V-MODEL - Rangga Rangga; Yuda Syahidin; Meira Hidayati (Jurnal Sistem Informasi dan Sains Teknologi, 2021)
This research aims to identify the design of information systems of outpatient medical record completeness by V-Model Method.Research methods used is qualitative method with descriptive approach. Data collection techniques used are by of observation, interviews, and the study of the literature. A method of software development model used the V-Model. From this research  found a problems there are still many unfilled outpatient medical record files,  Input of the data is not optimal which is occured of many errors and many delays in delivery reports frequently.Therefore, there are  some suggestion that is  given to resolve the problems in the system of the completeness of  medical record file  providing the socialisation on the importance of filling the medical record completely and Creating the information systems which are integrate and effective more.